2013
DOI: 10.1111/bjh.12689
|View full text |Cite
|
Sign up to set email alerts
|

Nestin expression throughout multistep pathogenesis of multiple myeloma

Abstract: SummaryThe stem cell marker nestin (NES) is found in dividing cells of developing and regenerating tissues. Upon terminal differentiation, NES expression is diminished but may be re-expressed following injury or in cancer. Surprisingly, we recently confirmed NES as a tumour-specific marker for mature CD138 + 38 + plasma cells (PC) in multiple myeloma (MM). The present study analysed NES expression throughout the spectrum of MM developmental stages, starting with individuals with no haematological malignancy, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
0
17
1
Order By: Relevance
“…Despite the evidence provided by above study, we also found the direct evidence that detection rate in relapse MM patients is higher than that in NDMM patients all the time [5,21,28]. In an early study, the stem cell marker nestin strongly associated with the presence of 1q21 gain may play an important role in MM relapse [29]. Besides, a study in Beijing analysis a gene expression microarrays of 1878 MM patients and found that with the increase of the amplification level of 1q21, the expression level of BCAR3 which is a protein-coding gene associated with many tumors showed an overall downward trend, interestingly, the expression of BCAR3 gene was different statistically in the non-relapse group and the relapse group, and the expression in the non-relapse group was notably higher than that in the relapse group (P = 0.0023) [14].…”
Section: Discussioncontrasting
confidence: 68%
“…Despite the evidence provided by above study, we also found the direct evidence that detection rate in relapse MM patients is higher than that in NDMM patients all the time [5,21,28]. In an early study, the stem cell marker nestin strongly associated with the presence of 1q21 gain may play an important role in MM relapse [29]. Besides, a study in Beijing analysis a gene expression microarrays of 1878 MM patients and found that with the increase of the amplification level of 1q21, the expression level of BCAR3 which is a protein-coding gene associated with many tumors showed an overall downward trend, interestingly, the expression of BCAR3 gene was different statistically in the non-relapse group and the relapse group, and the expression in the non-relapse group was notably higher than that in the relapse group (P = 0.0023) [14].…”
Section: Discussioncontrasting
confidence: 68%
“…40 , 41 Interestingly, the use of nestin as a predictive marker of a poor response to conventional therapy and to novel therapeutic agents was recently reported for multiple myeloma. 42 …”
Section: Nestin Expression In Transformed Cellsmentioning
confidence: 99%
“… 44 Furthermore, an association between increased nestin expression and the pathogenesis of multiple myeloma has been reported. 42 …”
Section: Nestin Expression In Transformed Cellsmentioning
confidence: 99%
“…Since NES levels correlate with tumor grade and represent a marker of cancer stem cells, it is presumed that NES also plays a role in carcinogenesis. Svachova et al (44) analyzed the occurrence of NES throughout the pathogenesis of MM, including patients with no hematological malignancy and MGUS. They showed that NES is differentially expressed in both patients with MM and MGUS.…”
Section: Accepted Manuscriptmentioning
confidence: 99%